Naturally Occurring Genetic Variants of Human Caspase‐1 Differ Considerably in Structure and the Ability to Activate Interleukin‐1β. Issue 1 (10th August 2012) - Luksch, Hella; Romanowski, Michael J.; Chara, Osvaldo; Tüngler, Victoria; Caffarena, Ernesto R.; Heymann, Michael C.; Lohse, Peter; Aksentijevich, Ivona; Remmers, Elaine F.; Flecks, Silvana; Quoos, Nadine; Gramatté, Johannes; et al.
<x xml:space="preserve">Abstract</x> Caspase‐1 (Interleukin‐1 Converting Enzyme, ICE) is a proinflammatory enzyme that plays pivotal roles in innate immunity and many inflammatory conditions such as periodic fever syndromes and gout. Inflammation is often mediated by enzymatic activation of interleukin (IL)‐1β and IL‐18. We detected seven naturally occurring human CASP1 variants with different effects on protein structure, expression, and enzymatic activity. Most mutations destabilized the caspase‐1 dimer interface as revealed by crystal structure analysis and homology modeling followed by molecular dynamics simulations. All variants demonstrated decreased or absent enzymatic and IL‐1β releasing activity in vitro, in a cell transfection model, and as low as 25% of normal ex vivo in a whole blood assay of samples taken from subjects with variant CASP1, a subset of whom suffered from unclassified autoinflammation. We conclude that decreased enzymatic activity of caspase‐1 is compatible with normal life and does not prevent moderate and severe autoinflammation.